Partial quadrate lobectomy improves early outcomes of laparoscopic Kasai surgery in type III biliary atresia - Chunhui Gu; Chunhui Gu; Chunhui Gu; Jian Sun; Lihong Ding; Lihong Ding; Bing Li; Youcheng Zhang; Guoqing Jiang; Guoqing Jiang (Frontiers in Pediatrics)
ObjectiveTo evaluate the early efficacy and safety of partial quadrate lobectomy during laparoscopic Kasai surgery for type III biliary atresia.MethodsThis retrospective study included 25 children diagnosed with type III biliary atresia, who underwent laparoscopic Kasai surgery between February 2018 and July 2022. Patients were divided into two groups: one with partial quadrate lobectomy and the other without. Data collected included age, gender, weight, incidence of cholangitis before and after surgery, one-year native liver survival, intraoperative blood loss, surgery duration, and jaundice clearance at 6 and 12 months. Follow-up results were compared between the groups.ResultsThe partial quadrate lobectomy group (14 patients) had a mean weight of 5.50 kg and average age of 66.79 days, while the control group (11 patients) had a similar weight (5.50 kg) and a mean age of 71.09 days. Weight comparison showed no significant difference (5.50 kg vs. 5.50 kg, P = 0.427). One-year postoperative native liver survival was 9/14 in the partial quadrate lobectomy group vs. 6/11 in the control group (P = 0.654).Intraoperative blood loss was similar between groups (P > 0.05), but the shorter operative time (301 vs. 347 min) associated with partial quadrate lobe resection may reduce anesthesia-related risks in infants, particularly given their limited physiological reserve. The reduced cholangitis rate (29% vs. 73%) aligns with prior reports suggesting that improved hilar exposure facilitates more precise dissection of fibrotic remnants, potentially minimizing postoperative bile stasis and infection. Jaundice clearance (defined as TBIL <20 μmol/L) was achieved in 8/14 (57.1%) of the partial quadrate lobectomy group vs. 3/11 (27.3%) in the control group at 6 months (P = 0.025), and 10/14 (71.4%) vs. 4/11 (36.4%) at 12 months (P = 0.031). The lower TBIL levels (5.11 vs. 9.67 mg/dl) at 6 months suggest enhanced bile drainage efficacy, which is critical for delaying or avoiding liver transplantation in this population.ConclusionPartial quadrate lobectomy during laparoscopic Kasai surgery reduces operation time, lowers cholangitis incidence, and improves jaundice clearance rates without increasing intraoperative blood loss or adversely affecting one-year native liver survival. It is a safe and feasible adjunct to improve early postoperative outcomes.